Project-Based Learning with a Deep Learning Approach on Students' Critical Thinking - Septina Anggraini; Ibnu Hajar (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2026)
Ecology learning is still often taught conventionally with a focus on rote memorization, resulting in insufficient training of students' critical thinking skills in addressing contextual environmental problems. This study offers novelty by integrating an eco-enzyme production project as a solution for managing organic school waste with a Deep Learning approach into the Project Based Learning (PjBL) model, an area that has not been widely studied in junior high school (SMP) science education. This study aims to determine the effect of project-based science learning using eco-enzymes with a Deep Learning approach on students' critical thinking skills in ecology material at SMP Negeri 25 Pekanbaru. This study employed a quantitative approach with a quasi-experimental method using a Nonequivalent Control Group Design. The research sample consisted of two seventh-grade classes selected through purposive sampling, one as the experimental class and one as the control class. Data were collected through written tests in the form of pretests and posttests, then analyzed using the Mann-Whitney U Test after the data were found not to be fully normally distributed. The results showed that the mean posttest score of the experimental class was 86.52, higher than that of the control class at 76.08, with an Asymp. Sig. (2-tailed) value of 0.000 (< 0.05), indicating that H0 was rejected and H1 was accepted, along with an effect size of 0.602, indicating an effect in the large category. These findings provide a scientific contribution in the form of empirical evidence that integrating real environmental issue-based projects with Deep Learning principles can serve as an effective strategy for training critical thinking skills in ecology material. Practically, this study implies the need for science teachers to develop contextual projects based on school environmental problems as an alternative learning approach that not only improves cognitive learning outcomes but also fosters students' environmental awareness as a foundation for 21st-century skills.